Delirium and Evidence-Based Nursing Practices: Covid-19 Pandemic Updates - Gülşah Kayserilioğlu; Nedret Tekin Kaya (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Delirium is a complex neuropsychiatric syndrome characterized by an acute onset of cognitive, attention, disorientation and change in the level of consciousness. Delirium is a serious health problem that is common at all ages and medical conditions in many places from the emergency department to the operating room. Delirium symptoms can develop within hours or days and last longer than a month. Nurses have important roles in diagnosing delirium and managing the process with evidence-based practices in patient care. Delirium screening and diagnostic measurement tools used for delirium risk classification and diagnosis should be used by nurses who care for the patient day and night. High mortality in the delirium table, a long stay in the intensive care unit or in the hospital lead to high maintenance costs. The prevalence rates of delirium in patients with Covid-19 have increased. The triggering factors that cause delirium in the Covid-19 pandemic may be social distance and social isolation, deep sedation practices, high fever, prolonged mechanical ventilation, delayed extubation due to aerosol propagation anxiety, inadequate pain assessment, psychological perceptions (mass death), multiple organ dysfunctions. It is known that the application of the ABCDEF (Assessing Pain, Both Spontaneous Awakening and Breathing Trials, Choice of Drugs, Delirium monitoring/management, Early exercise/mobility, and Family Empowerment) care package is effective in the management of delirium. It is recommended to use the ABCDEF care package for delirium management in Covid-19 patients. In this review, evidence-based practices are included in the prevention of delirium and nursing care in the coronavirus (SARS-CoV-2) pandemic affecting the whole world. (JNNN 2022;11(2):74–82).